우드세라믹 제조용 석탄산수지 함침보드의 수지 함침율과 치수 증가율 - 증기분사 시간의 영향 - 오승원; Seung Won Oh (목재공학, 2002)
The properties of new porous carbon materials "Woodceramics" are affected by the characteristics of raw boards. To investigate of density profile and resin contents in impregnated boards, control board and 3 types of steam-injected boards were made by steam injection time, The wood species used for manufacturing boards was Sugi(Cryptomeria japonica). The results are as follows: 1) The density gradient of board after 10 minutes steam injection was the smallest and non-steamed board was largest. 2) The resin content and dimensional rise decreased with increase of board density, and were the largest in board after 10minutes steam injection but there was little difference between boards after 5 and 10 minutes steam injection. 우드세라믹의 성질에 영향을 미치는 보드의 수지 함침율과 밀도경사의 특성을 알아보기 위하여 증기 처리를 하지 않은 보드와 증기 처리를 1, 5, 10분 실시한 보드를 석탄산수지로 함침한 후 증기분사 시간의 영향을 조사하였다. 증기처리를 하지 않은 보드의 중층과 표층의 밀도 비가 가장 컸으며, 수지 함침율, 길이 및 두께 증가율은 밀도가 증가함에 따라 감소하였다. 또한 등기처리를 10분 실시한 보드의 수지 함침율, 길이 및 두께 증가율이 가장 컸다.